(untitled) (Gaceta Técnica, 2024)
Given the excessive increase in concrete constructions that is currently occurring, the presence of cracking and collapse problems has directly affected its durability, stability and longevity, being a constant concern for citizens and the engineering sector, therefore, in this paper, the objective of evaluating concrete by applying limestone aggregates from the Trapiche quarry along with the addition of ground rubber with the purpose of improving the base physical-mechanical properties that it has. For which, it is proposed as an investigative methodology of experimental nature and design through a quantitative approach, evaluating concrete specimens prepared under the standard of the American Concrete Institute (A.C.I.) 211 to meet the objective of improving the physical-mechanical properties of sustainable concrete. The results obtained in the study showed that, in the resistance tests at 28 days in simple compression effects, the concrete group 0 (G0) compared to group 1 (G1) of 2,7% ground rubber (CM) obtained a resistance of 22,40 MPa, while in the bending tests it reached a bending value of 5.01 MPa with the addition of 2,7% of ground rubber. However, for the physical concrete settlement tests, it was evident that CM improves all the experimental samples by 6,67%, with the highest improvement value proposed by group 2 (G2) and 3 (G3) with 4 ¼” inches, with a 3 ¾” pattern